2021
DOI: 10.1071/cp21059
|View full text |Cite
|
Sign up to set email alerts
|

Selenium desorption in tropical soils by sulfate and phosphate, and selenium biofortification of Mombaça grass under increasing rates of phosphate fertilisation

Abstract: Selenium (Se) is essential for animals and humans, and studies assessing the influence of sulfur (S) and phosphorus (P) on Se availability and biofortification in tropical soils are required. This study evaluated the adsorption of selenate (SeVI) and selenite (SeIV) in two oxidic soils with contrasting soil texture and assessed effects of phosphate and sulfate as competitive anions on Se desorption. The study also examined Se biofortification of Panicum maximum cv. Mombaça grown in Se-treated clayey soil under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…P starvation had no effect on selenate uptake but decreased selenate concentration in the xylem sap of selenate-treated plants in hydroponic experiments [ 11 ]. Some studies reported that P application increased the utilization of selenate and then increased the Se contents in plants [ 29 , 30 ]. Compared with the numerous studies on inorganic Se, few studies have focused on the uptake of organic Se influenced by P application in plants.…”
Section: Introductionmentioning
confidence: 99%
“…P starvation had no effect on selenate uptake but decreased selenate concentration in the xylem sap of selenate-treated plants in hydroponic experiments [ 11 ]. Some studies reported that P application increased the utilization of selenate and then increased the Se contents in plants [ 29 , 30 ]. Compared with the numerous studies on inorganic Se, few studies have focused on the uptake of organic Se influenced by P application in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [47] demonstrated that P and Se absorption in the form of selenite presents antagonistic behavior, in which the increase in the P supply significantly decreased the Se concentration in the roots, stems, and leaves of winter wheat, justifying that the presence of P and S influences Se bioavailability in various plant tissues. However, Santos et al [48] and Zhang et al [49] observed in Panicum maximum cv. Mombaça and wheat plants, respectively, that the way Se is present in the soil influences the synergism with P, i.e., there is an accumulation of both elements only when Se is applied as selenate.…”
Section: Discussionmentioning
confidence: 95%
“…The average Se content found in the studied soil (0.73 mg dm −3 ) is within the range of Se contents reported for soils of the State of São Paulo (where the Uva farm is located), which varies from <0.08–1.61 mg dm −3 . Soil Se content is influenced by characteristics such as pH ( Schiavon et al, 2020 ), presence of competing ions such as sulfate and phosphate ( Lessa et al, 2016 ; Santos et al, 2022 ), soil texture ( Araujo et al, 2018 ), organic matter ( Li et al, 2017 ), and presence of microorganisms ( Gregorio et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%